Bioinformatics study of well established markers of oxidative stress for further molecular applications in coral, its symbionts and other associated species in Singapore. - Chen, Belinda Jinyu. (2012)
In the context of coral reef ecosystems, oxidative stress, which results from the over damaging effects of reactive oxygen species (ROS) in the cell, has been linked to worldwide mass coral mortality events. Several studies were conducted on corals on ROS detoxifying cellular antioxidant enzymes. However, no data are available on the antioxidant systems on corals in Singapore. This project aimed at providing genetic and proteic information on two main antioxidant enzymes (catalase and thioredoxin), to determine their suitability as early oxidative stress diagnostic markers in Singapore coral ecosystems, and design primers for their gene expression study. The bibliography search highlights several oxidant factors, mostly temperature related, causing up-regulation of catalase and thioredoxin gene expression. Conservation of several important motif sites needed for functional three-dimensional folding of proteins was also observed for both proteins. From these data, catalase and thioredoxin appear as suitable oxidative stress diagnostic markers in coral ecosystems. Primers were designed to target specifically either coral or zooxanthellae. After sampling of corals in Singapore, DNA and RNA were extracted and preliminary PCR test was run. Further analysis may conclude on the specificity and efficiency of the designed primers to be use as early warning tool in coral reefs.